Effect of Good Hygiene Sanitation and Personal Hygiene Depot Management of Refill Drinking Water on the Quality of Drinking Water Reviewed from Most-Probable-Number Coliform in Kediri - Indasah, Indasah (Folia Medica Indonesiana, 2018)
Drinking water is a basic human need and must meet health requirements. Drinking water depots are a means of filling drinking water which is in the process of processing raw water using treatment and sterilization system. Drinking water depots as providers of drinking water must also meet the requirements of sanitation hygiene and personal hygiene management must also be maintained so that the water produced meets health requirements. The purpose of this study was to determine the effect of sanitation hygiene and personal hygiene management of refill drinking water depots on the quality of drinking water in terms of the Most Probable Number Coliform in Kediri. The research design used was analytic observational with cross sectional approach. The population of all refill drinking water depots in Kediri is 57, with the sampling technique that is Simple Random Sampling, where a portion of refill drinking water depots in Kediri are 50. Data is collected by check list, questionnaire and laboratory examination. The results showed that most of the hygiene sanitation of the drinking water depot had fulfilled the requirements of 77%, the drinking water personal hygiene depot was good as much as 85% and those who met the drinking water requirements were 70%. The results of the hygiene feasibility analysis showed the value of Sig 0.000<0.05 (R=0.935) means that there was an effect of hygiene sanitation quality with water quality in terms of the Most Probable Number Coliform. While the personal hygiene value of Sig 0.001 <0.05 (R = 0.528) indicates that there is a personal hygiene influence with water quality in terms of the Most Probable Number Coliform. The results of Logistic Regression test showed that there were effects of sanitation hygiene and personal hygiene management of refill drinking water depots with water quality in terms of the Most Probable Number Coliform with a significance value = 0.000